Are prophylactic antibiotics effective for preventing infection after first‐trimester abortion?. Issue 9 (September 2017) - Choudhary, Kriti; Madlon‐Kay, Diane J.
Abstract : EVIDENCE‐BASED ANSWER : Antibiotic prophylaxis given preprocedure at the time of first‐trimester surgical abortion is an effective strategy for reducing the risk of infection and is recommended (SOR: A, meta‐analysis). For medical abortions, the routine use of prophylactic antibiotics is not recommended (SOR: B, systematic review‐based guidelines).